Enhancing Professional Fluency: Leveraging Discourse Markers and Fluencemes in Vocational English Presentations - Aprillianti, Linda; Wulandari, Astri; Alif, Wening Nur Habibah; Adhelia, Shafira; Wardati, Rifka Uzma (Universitas Pahlawan Tuanku Tambusai, 2026)
Oral fluency is a vital competency for Business Administration students in global settings. However, the synergy between discourse markers (DMs) and fluencemes in vocational assessments remains under-researched. This qualitative study explicitly addresses: (1) what types of DMs and fluencemes appear in students' presentations; (2) what functional purposes these markers serve; and (3) how they influence message clarity and coherence. Analyzing nine speech transcripts from Semarang State Polytechnic via Crible’s (2018) DisFrEn framework , findings reveal that DMs and fluencemes act as strategic cognitive resources rather than mere errors. Students employ tactics like